The Prognostic Performance of Rotational Thromboelastometry for Excessive Bleeding and Increased Transfusion Requirements in Hip Fracture Surgeries - Tsantes, Andreas G.; Papadopoulos, Dimitrios V.; Trikoupis, Ioannis G.; Tsante, Konstantina A.; Mavrogenis, Andreas F.; Koulouvaris, Panagiotis; Vaiopoulos, Aristeidis G.; Piovani, Daniele; Nikolopoulos, Georgios K.; Kokoris, Styliani I.; Bonovas, Stefanos; Papagelopoulos, Panayiotis J.; Tsantes, Argirios E. (Thrombosis and Haemostasis, 2021)
Background Hip fracture surgeries are associated with considerable blood loss, while the perioperative coagulopathy is associated with the bleeding risk of these patients. We aimed to evaluate the ability of rotational thromboelastometry (ROTEM) to detect patients at high risk for excessive bleeding and increased transfusion requirements.Methods We conducted a prospective observational study of 221 patients who underwent hip fracture surgeries. ROTEM analysis was performed preoperatively and immediately postoperatively. Blood loss parameters including blood loss volume, number of transfused red blood cell (RBC) units, and drop in hemoglobin levels were recorded. ROTEM parameters were compared between patients with and without excessive bleeding, and between patients with and without increased transfusion requirements (i.e., ≥2 RBC units).Results The postoperative FIBTEM MCF value ≤15 mm had 66.6% (95% confidence interval [CI]: 59.7–74.1%) sensitivity and 92.0% (95% CI: 80.7–97.7%) specificity to prognose excessive bleeding, and preoperative FIBTEM MCF value ≤15 mm had 80.4% (95% CI: 73.5–86.2%) sensitivity and 91.2% (95% CI: 80.7–97.0%) specificity to prognose increased transfusion requirements. Preoperative FIBTEM MCF ≤11 mm and postoperative FIBTEM MCF ≤15 mm were associated with considerably increased risks of excessive bleeding (odds ratio [OR]: 44.8, 95% CI: 16.5–121.3, p < 0.001; and OR: 23.0, 95% CI: 7.8–67.0, p < 0.001, respectively).Conclusion ROTEM parameters demonstrated high prognostic accuracy for excessive bleeding and increased transfusion requirements. This can enable implementation of blood sparing strategies in high-risk patients, while blood banks could be better prepared to ensure adequate blood supply.
Keywords: transfusion; bleeding risk; coagulopathy; rotational thromboelastometry; hip fractures